2021
DOI: 10.3390/v13050742
|View full text |Cite
|
Sign up to set email alerts
|

Accessible LAMP-Enabled Rapid Test (ALERT) for Detecting SARS-CoV-2

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has highlighted bottlenecks in large-scale, frequent testing of populations for infections. Polymerase chain reaction (PCR)-based diagnostic tests are expensive, reliant on centralized labs, can take days to deliver results, and are prone to backlogs and supply shortages. Antigen tests that bind and detect the surface proteins of a virus are rapid and scalable but suffer from high false negative rates. To address this problem, an inexpensive, simple, and robust … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…In the current OmniLAMP R assay, we included human b-actin RNA (rACTB) as internal control. Other constitutive targets for SARS-CoV-2 RT-LAMP include BPIFA1 (Bektaş et al, 2021) Similar to its high sensitivity, obtained in this work and by other studies, the SARS-CoV-2 RT-LAMP specificity is undoubtedly high and is frequently reported as 100% without any cross-reactivity with other respiratory or SARS-CoV-unrelated viruses (Chow et al, 2020;Mohon et al, 2020;Park et al, 2020;Aoki et al, 2021;Nawattanapaiboon et al, 2021). We also confirm that the SARS-CoV-2 RT-LAMP solution presented here is highly specific and does not cross-react with Brazilian occurring seasonal influenza A and B, hRSV, or arboviruses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current OmniLAMP R assay, we included human b-actin RNA (rACTB) as internal control. Other constitutive targets for SARS-CoV-2 RT-LAMP include BPIFA1 (Bektaş et al, 2021) Similar to its high sensitivity, obtained in this work and by other studies, the SARS-CoV-2 RT-LAMP specificity is undoubtedly high and is frequently reported as 100% without any cross-reactivity with other respiratory or SARS-CoV-unrelated viruses (Chow et al, 2020;Mohon et al, 2020;Park et al, 2020;Aoki et al, 2021;Nawattanapaiboon et al, 2021). We also confirm that the SARS-CoV-2 RT-LAMP solution presented here is highly specific and does not cross-react with Brazilian occurring seasonal influenza A and B, hRSV, or arboviruses.…”
Section: Discussionmentioning
confidence: 99%
“…In the current OmniLAMP ® assay, we included human b-actin RNA (rACTB) as internal control. Other constitutive targets for SARS-CoV-2 RT-LAMP include BPIFA1 ( Bektaş et al, 2021 ), human 18S RNA ( de Oliveira Coelho et al, 2021 ), and Statherin RNA ( Sherrill-Mix et al, 2021a ; Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For application in a dedicated diagnostic laboratory environment there are different protocols available using fluorescence detection, or absorbance readings as quantitative measurement 27 33 . These advanced detection methods are also possible in POCT diagnostics and several protocols are available 34 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The rest of the methods predominantly are either whole nucleic acid extraction or immunomagnetic capture followed by lysis. The former also included all magneto-extraction associated SARS-CoV-2 detection techniques using LAMP (entries 7, 10, 14, 24, 35, 48, Table S1 25,[33][34][35][36][37] ). Surprisingly, none of these studies listed in Table S1 utilized electrochemical readout despite its promising potential in limited resource detection.…”
Section: Introductionmentioning
confidence: 99%